Locoregional metastatic behavior in a complex mosaic of primary malignant tumors of the parotid gland - Varga, Regina; Iro, Ann Kristin; Thimsen, Vivian; Sievert, Matti; Agaimy, Abbas; Balk, Matthias; Rupp, Robin; Grundtner, Philipp; Koch, Michael; Iro, Heinrich; Mantsopoulos, Konstantinos (American Journal of Otolaryngology, 2023)
Background: The aim of the study was to investigate primary locoregional metastatic behavior in a large sample of various malignant tumors of the parotid gland with varying grades following surgical treatment consisting of complete parotidectomy and neck dissection. Methods: The records of all patients treated for primary malignant tumors of the parotid gland by means of complete parotidectomy and neck dissection between 2007 and 2022 were studied retrospectively. Results: 196 patients formed our study sample (98 females, 98 males). The mean age was 65.7 years (22–101 years). 92 cases presented with low-grade subtypes, 19 with intermediate-grade, and 85 with high-grade carcinomas. The locoregional lymphatic network had been invaded in a total of 66/196 cases (33.6 %). The intraparotid lymph nodes were positive in 54/196 cases (27.5 %) and the cervical lymph nodes in 41/196 cases (20.9 %). In 12 out of the 66 cases with a pN+ status, the neck had been invaded without involvement of the intraparotideal lymph nodes (18.2 %). Male patients tended to suffer from more aggressive carcinomas, and high-grade subtypes presented significantly more frequently as locally advanced tumors. Higher grading was significantly associated with the involvement of the parotid (p < 0.001) and cervical (p < 0.001) lymph nodes. Intermediate and low-grade cases presented similar behavior concerning tumorous invasion of the lymphatic network of the parotid gland (p = 0.522) and the neck (p = 0.467). Conclusion: The locoregional metastatic potential of parotid malignant tumors depends upon a variety of histopathologic factors, which have to be considered in the decision-making process concerning the management of locoregional lymph nodes.
CRIS-Team Scopus Importer:2023-07-21
Keywords: High-grade; Low-grade; Malignant tumor; Neck dissection; Parotid gland; Parotidectomy